1992
DOI: 10.1093/clinchem/38.5.704
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde Kit Evaluated for Determining Plasma and Lipoprotein Fractions that React with Thiobarbituric Acid

Abstract: The determination of thiobarbituric acid reactants (TBARs) is a widely used method for investigating overall lipid peroxidation. An assay kit that could be used with plasma and lipid fractions would facilitate standardization of the method. The results reported here indicate that the malondialdehyde (MDA) kit manufactured by Sobioda (Grenoble, France) complies with criteria of good analytical practices. The detection limit was 0.11 mumol of MDA per liter of plasma. The within-run (CV = 1.8-3.3%) and between-ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(100 citation statements)
references
References 0 publications
3
96
1
Order By: Relevance
“…Lipid peroxidation (LP) in nuclear and cytoplasmic extracts was quantified by measuring the concentration of TBARS by a spectrofluorometric assay using a 'TBARS assay kit' at an exitation wavelength of 532 nm and emission wavelength of 553 nm with the same endpoints by Richard et al (1992). Quantification was achieved by parallel measurements of a standard curve of known TBARS concentrations, and the results were expressed as nmol g À1 protein.…”
Section: Determination Of Lipid Peroxidationmentioning
confidence: 99%
“…Lipid peroxidation (LP) in nuclear and cytoplasmic extracts was quantified by measuring the concentration of TBARS by a spectrofluorometric assay using a 'TBARS assay kit' at an exitation wavelength of 532 nm and emission wavelength of 553 nm with the same endpoints by Richard et al (1992). Quantification was achieved by parallel measurements of a standard curve of known TBARS concentrations, and the results were expressed as nmol g À1 protein.…”
Section: Determination Of Lipid Peroxidationmentioning
confidence: 99%
“…This measure was performed using the Sobioda TBARS kit (Grenoble, France) as described by Richard et al . [12], in which the fluorescence of thiobarbituric acid (TBA) reactants in plasma is recorded. The reagents in the kit consisted of TBA, perchloric acid and a calibration solution consisting of 1,1,3,3-tetraethoxypropane (TEP), 20 mmol L − 1 , in ethanol.…”
Section: Assessment Of Selenium Level and Antioxidant Enzyme Activitymentioning
confidence: 99%
“…An important advantage of fluorometry relies on its great increase in sensitivity in relation to HPLC with absorbance detection (Iwata & Kikugawa 1987;Knight er al. 1987;Wong et al 1987;Richard et al 1992). The lower sensitivity of the measurement of thiobarbituric acid reactive substances by spectrophotometry leads to the need of concentrating human urine previously to detection of diethylthiobarbituric acid reactive substances by HPLC with absorbance detection at 532 nm (Guichandart et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the fluorescence measurement of thiobarbituric acid reactive substances eliminates interferences from various substances (Okawa et al 1979;Bird & Draper 1984). It has been demonstrated that the direct fluorescence measurement of thiobarbituric acid reactive substances in human plasma highly correlates with thiobarbituric acid reactive substances measured in the same plasma samples by HPLC with absorbance detection at 532 nm (r=0.8; P<O.OOOl; Richard et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation